Harmonizing business wisdom in managing social enterprises - Ismail, Yusof; Mhd. Sarif, Suhaimi (2015)
Knowledge may be perceived positively, negatively or neutrally depending on one’s belief or profession. Since knowledge is generally no individual’s monopoly it may be acquired, processed, retained, utilized and disseminated by anyone and anywhere, individually or institutionally. Knowledge may be associated with wisdom (al-hikmah) although the latter goes beyond knowledge. Islam encourages its followers to benefit from available knowledge, concepts, theories and practices. Knowledge reflects wisdom. Realistic Muslims strive to benefit from useful knowledge and practices that represent wisdom irrespective of their origin and age. Non-profit organizations or social enterprises can benefit from the wisdom of management thoughts and practices of firms (companies, corporations), some of which were time tested. The study presents the concept of wisdom and it spirit from Islamic tradition. It solicited the opinions of Muslim undergraduates of a public university who were exposed to business courses about their perceptions of wisdom and knowledge and whether wisdom of others could be adapted for applications in organizations. For in-depth input, the study identified eight subjects based on the authors’ knowledge of the former’s background. Results of the study show that the subjects do have a grasp of the concept of wisdom, although the Islamic terminology al-hikmah was not used in the instrument at all. They do agree that knowledge and wisdom are inter-related but wisdom transcends knowledge. The subjects are mixed in their views pertaining to application of ‘borrowed’ wisdom in profit and non-profit organizations. Overall, results suggest that wisdom multiplies without boundaries.